Malaysia: National Language Policy and Employability - Selvaratnam, Viswanathan (International Higher Education, 2018)
Malaysia’s public–private sector university graduates are facing an employment crisis and their employability rates “remain poor and unimproved.” The low graduate employability is primarily due to their poor command of English, weak professional competency, lack of critical communication, interpersonal, and leadership skills, and a lacklustre work attitude. The mismatch between demand and supply of high-quality human capital from local universities is hampering the country’s aspiration to be a developed nation by 2020. Unemployable graduates are absorbed into the highly bloated public service, while private sector companies are recruiting almost exclusively among returnees of top overseas English-medium universities.